Persepsi dan Partisipasi Masyarakat Terhadap Pengelolaan Sampah Rumah Tangga melalui TPS 3R Sulur Berkah dan Makmur Jaya di Kota Jambi - Heryeni, Siti Sholeha Anggunisa; Syarifuddin, Hutwan; Ilham, Ilham (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
One of the waste reduction efforts carried out by the Jambi City Government is the provision of 3R TPS. The reduction target set by the government until 2030 is 30%. Community participation is really needed to reduce and/or handle waste in an environmentally sound manner, including efforts to sort waste from the source. Waste sorting that is not carried out at the source can result in mixed waste and reduce the economic value of recycled waste. Apart from that, sufficient human resources and a long time are needed to sort the waste at TPS 3R, while the residue must be immediately transported to the TPA so as not to cause a bad smell and discomfort for local residents. Internal conflicts at TPS 3R regarding financial management and several other things resulted in TPS 3R not functioning according to its function. The aim of this research is to examine community perceptions and participation in household waste management through TPS 3R Sulur Berkah and Makmur Jaya in Jambi City. The research method used is descriptive analysis and the main data collection tool is a questionnaire. The research instrument uses a Likert scale with 4 (four) response options. The research results show that 100% of respondents have a positive perception of household waste management through TPS 3R. However, only 62% have high participation in household waste management, the remaining 38% of respondents have low participation.